Pemanfaatan Pekarangan Perumahan Kota Dengan Program Lingkungan Rumah Toga Dan Pangan - Adi Budiwan (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
LRTP is a food and food environment. Diversification of food through the use of local land-based land. In addition, the concept of environmentally friendly and independent food is also developed to meet family needs, as well as the efficiency of family expenses. This concept needs to be carried out so that the LRTP program can be used as a community for all residents in the village of Babat Jerawat, with the aim of: (1) Socializing and inviting the Babat Jerawat villagers to create a Food and Food Home Environment (LRTP). (2) Establishment of environmental groups that can support implementation (LRTP), as well as other programs. The training was conducted at RT 03 and 4 Babat Jerawat villages, Pakal sub-district, Surabaya with a participatory approach using encouragement and invitations to local cadets. The results of the coordination show that: (1) the community is very active in welcoming and implementing the LRTP program. (2) The community has succeeded in forming a group called the Toga and Food Group (KTP), which will succeed the LRTP program further.